Interpretation of Ground Penetrating Radar (Gpr) to Determine the Depth of Pipe Objects in the Sandbox - Dwi Sri Wahyudi; Rini Kusumawardani (Jurnal Teknik Sipil dan Perencanaan, 2024)
Ground Penetrating Radar (GPR) is a non-destructive inspection technology that utilizes electromagnetic (EM) waves to map subsurface structures. This study focuses on estimating the diameter and depth of buried cylindrical objects, especially pipes, using GPR. This research was carried out through laboratory experiments using a box filled with dry sand. GPR data is processed using matGPR software to analyze hyperbolic reflections generated by buried objects. matGPR is software used for mathematical calculations of all three software. The speed of the EM wave is calculated based on the dielectric properties of the sand, and the depth and diameter of the pipe are estimated using a mathematical model derived from hyperbolic reflection. The results showed that the pipe depth estimate had a low error percentage, generally below 5%, which indicated high accuracy in GPR measurements, pipe A showed an estimated depth of 16.2 cm with the result obtained an error percentage of 1.8%, pipe B showed an estimated depth of 15.3 cm with the result obtained an error percentage of 1% and pipe C showed an estimated depth of 13.7 cm with the result obtained The error percentage is 2.2 %.The study concludes that GPR is an effective tool for estimating the depth of buried objects, especially in a controlled environment such as a sandbox. However, factors such as burial depth, pipe material, and dielectric properties of the medium can affect the accuracy of the measurement. Future research should consider using varied pipe materials and deeper burial depths to further validate the reliability of this method under field conditions.